GPTS DAN MASA DEPAN EKONOMI INDONESIA - I Putu Hedi Sasrawan; Gede Crisna Wijaya (BORJUIS: JURNAL OF ECONOMY, 2025)
This study explores the role of General Purpose Technologies (GPTs) as fundamental drivers of long-term economic transformation and analyzes the prospective impact of Artificial Intelligence (AI) on the future of the Indonesian economy. GPTs, characterized by their pervasiveness, continuous improvement, and ability to foster complementary innovations, historically trigger profound structural changes. However, their full productivity benefits are often delayed, a phenomenon known as the "productivity paradox," pending significant co-investments in complementary assets such as human capital, infrastructure, and institutional adaptation. Indonesia's experience with the internet, where significant economic impact materialized only in the long term, serves as a pertinent case study. As the world enters a new wave driven by AI—a GPT with the unprecedented potential to automate cognitive tasks—Indonesia faces both a monumental opportunity for growth acceleration and substantial risks of deepening inequality and labor market dislocation. Through a qualitative literature review , this paper argues that successfully navigating the AI era demands a comprehensive national strategy. This strategy must transcend mere technological adoption to prioritize a fundamental reform of the education system towards automation-resistant skills, ensure equitable digital infrastructure development, and establish an adaptive ethical and regulatory framework. Ultimately, the paper concludes that a holistic, human-centric approach is crucial for Indonesia to leverage AI for inclusive and sustainable economic growth.